A digital literacy model to narrow the digital literacy skills gap. Issue 4 (April 2023) - Reddy, Pritika; Chaudhary, Kaylash; Hussein, Shamina
Abstract: The concept of digital literacy is increasingly prevalent in the 21st century. Growing demands from the work sector for individuals to be digitally literate has prompted targeted interventions and innovations from the education sector to instil digital skills into the future workforce. However, despite efforts the digital skills gap remains visible globally. This paper explores the prominent educational frameworks and models, their advantages and limitations in 21st-century learning and teaching. Furthermore, a new innovative digital literacy model has been proposed to be integrated into the existing and future education frameworks and models to assist educationists in narrowing the digital skills gaps and preparing graduates for the work sector. The digital literacy model consists of two components: (1) the digital literacy framework- South Pacific Digital Literacy Framework (SPDLF) and (2) the digital literacy tool. The SPDLF reflects six major literacies identified for the 21st-century while the digital literacy tool– digilitFJ consists of a digital literacy measuring scale and an online intervention program. The exploratory factor analysis showed that the SPDLF was valid. On the other hand, heuristics, student attitude, and satisfaction and effectiveness of the digital literacy tool were also evaluated from the student's perspective to reflect its usefulness. The survey results also showed a positive attitude and perception of the use of the tool. Additionally, Cohen's d value showed that the digital literacy tool was effective. Therefore, if the tool is implemented and adopted, it can narrow the existing digital skills gap in the South Pacific.